Stakeholder perceptions and policy implications of voluntary and government-led individual quota systems in japanese fisheries co-management: A case study of purse seine fisheries in the sea of Japan - Yudai Hanzawa; Shingo Watari; Shion Takemura (Marine Policy, 2024)

Correction: Impacts of regime shift on the fishery ecosystem in the coastal area of Kyoto prefecture, Sea of Japan, assessed using the Ecopath model - Hiroshi Inoue; Shingo Watari; Hideki Sawada; Edouard Lavergne; Yoh Yamashita (Fisheries Science, 2024)

Charting and analyzing the catch distribution of Japan’s coastal fisheries resources based on centennial statistics - Shingo Watari; Shion Takemura; Hitomi Oyaizu (Frontiers in Marine Science, 2024)
Spatiotemporal changes in catches and transition of fishing grounds have been observed in various coastal fishery resources in Japanese waters in recent years. Are these changes part of cyclical fluctuations on a centennial timescale? Are these changes situations that have never been observed prior to this? Are common factors included in the long-term fluctuations among coastal fisheries resources? A total of 12 important Japanese coastal fisheries resources including fishes, shells, invertebrates, and algae were analyzed using fisheries statistics on the geographical center of catch compiled since 1894. The time series of the geographical center of catch showed a cyclical fluctuation trend over time rather than changing monotonically. The geographic center of catch in recent years (2019–2021) was located at the northeastern margin of the distribution, compared to its location since the end of the 19th century for many fishery resources. For coastal fishery resources, the situation in terms of fluctuations in the geographical center of catch is more extreme than in the past 100 years. The results of the dynamic factor analysis suggested that the state of these resources may be affected by the global ocean environment and other factors including human activities. Examining how fisheries have responded to past cyclical fluctuations may provide insight into adapting to the current rapid changes caused by climate change.

Governance and science implementation in fisheries management in Japan as it compares to the United States - Siri Hakala; Shingo Watari; Shinji Uehara; Yujiro Akatsuka; Richard Methot; Yoshi Oozeki (Marine Policy, 2023)

Impacts of regime shift on the fishery ecosystem in the coastal area of Kyoto prefecture, Sea of Japan, assessed using the Ecopath model - Hiroshi Inoue; Shingo Watari; Hideki Sawada; Edouard Lavergne; Yoh Yamashita (Fisheries Science, 2023)
The present study assessed the impact of regime shifts on the ecosystems that support fisheries in the coastal area of Kyoto Prefecture, the Sea of Japan. Ecopath models were constructed during cold (1985) and warm (2013) regime periods, when the fishery structures were different. Both models evaluated by pre-balance diagnostics were reliably constructed. Multiple ecosystem indicator values were compared between the two periods to assess changes in the ecosystem structure and the impact of fisheries on the ecosystem. The major change in catches in the coastal area of Kyoto Prefecture between 1985 and 2013 was that the Japanese sardine drastically declined and Spanish mackerel increased. The primary production requirements of fisheries ( %PPR ) were higher in 1985, reflecting the greater impact of sardine. The mean trophic level of catch and system omnivory index suggested that stability of trophic network increased after the sharp decline in sardine biomass. The %PPR, the loss of secondary production due to fisheries exploitation and probability analysis of fishery sustainability suggested that the fishery structure in 2013, which was dominated by set nets, contributed to a more sustainable fishery than the structure in 1985, when fishery was dominated by purse seines and set nets.

Life in the fast lane: Revisiting the fast growth—High survival paradigm during the early life stages of fishes - Dominique Robert; Jun Shoji; Pascal Sirois; Akinori Takasuka; Ignacio A. Catalán; Arild Folkvord; Stuart A. Ludsin; Myron A. Peck; Su Sponaugle; Patricia M. Ayón; Richard D. Brodeur; Emily Y. Campbell; et al. (Fish and Fisheries, 2023)
Early life survival is critical to successful replenishment of fish populations, and hypotheses developed under the Growth‐Survival Paradigm (GSP) have guided investigations of controlling processes. The GSP postulates that recruitment depends on growth and mortality rates during early life stages, as well as their duration, after which the mortality declines substantially. The GSP predicts a shift in the frequency distribution of growth histories with age towards faster growth rates relative to the initial population because slow‐growing individuals are subject to high mortality (via starvation and predation). However, mortality data compiled from 387 cases published in 153 studies (1971–2022) showed that the GSP was only supported in 56% of cases. Selection against slow growth occurred in two‐thirds of field studies, leaving a non‐negligible fraction of cases showing either an absence of or inverse growth‐selective survival, suggesting the growth‐survival relationship is more complex than currently considered within the GSP framework. Stochastic simulations allowed us to assess the influence of key intrinsic and extrinsic factors on the characteristics of surviving larvae and identify knowledge gaps on the drivers of variability in growth‐selective survival. We suggest caution when interpreting patterns of growth selection because changes in variance and autocorrelation of individual growth rates among cohorts can invalidate fundamental GSP assumptions. We argue that breakthroughs in recruitment research require a comprehensive, population‐specific characterization of the role of predation and intrinsic factors in driving variability in the distribution and autocorrelation of larval growth rates, and of the life stage corresponding to the endpoint of pre‐recruited life.

Not satisfactory, but still acceptable: Exploring socioeconomic incentives of individual quota systems in Japanese Pacific bluefin tuna fisheries from the management leaders’ perspective - Yudai Hanzawa; Shingo Watari; Shion Takemura (Marine Policy, 2023)

Science-policy-public interface toward ocean sustainability: An empirical study using legal documents, scientific publications, and public inquiry logs in Japan - Aoi Sugimoto; Hidetomo Tajima; Takuma Sugaya; Shingo Watari (Frontiers in Marine Science, 2023)
Many countries have governmental fisheries science organizations, each of which should play a critical role in achieving ocean sustainability by leading the fisheries science in each country’s specific contexts and beyond. In the context of the UN Decade of Ocean Science (UNDOS), understanding the interface of science, policy, and public interest around fisheries is increasingly recognized as critically important for realizing effective knowledge exchange and co-creating desired futures. This study aims to illuminate the interface of the above three facets as a guide to have better outcomes in the UNDOS timeframe. We used a case study of Japan – a country with extensive seafood production and consumption, and analyzed 1) the scientific performance of the Japan Fisheries Research and Education Agency (JFRA), a national fisheries research organization in the country through peer-reviewed papers published by JFRA researchers from 2004–2018, 2) policy needs through annual white papers published by Fisheries Agency from 1989–2018, and 3) public interest around fisheries through public inquiry logs accumulated at JFRA from 2004–2018. The results indicated the following: 1) JFRA was originally a part of fisheries policies, and both science and policy were inherently based on the fisheries practices in the “real world” in Japan. However, over the last fifteen years, the scientific performance has heavily focused on bio-physical dimensions of fisheries such areas as “Stock assessment,” “Fisheries Oceanography,” and “Stock enhancement.” 2) Japanese fisheries policy priority has shifted from relatively simple, straightforward keywords focusing on primary fisheries production (from 1989 to 1998) to more complex, multidimensional fisheries systems, including marine resources, producers, processors, and consumers in/outside of the country (from 2009–2018) over the last three decades. 3) Public fisheries/ocean literacy seems limited, despite the rich history of seafood consumption, cultural bond with fisheries, and inherent close relationship among fisheries science, policy, and resource users. Based on the results, we discuss that JFRA sciences, fisheries policy, and the public are contemporary pursuing different interests. To overcome this situation, one important area that JFRA (and any other marine/fisheries research organizations) needs is to reconnect science and public interest through strengthening human dimension works and science communication. For the public side, literacy development among wider stakeholders is one of the most emergent works to be addressed. This is one of the first case studies of science-policy-public interface through empirical data, particularly with the public inquiry log, and the “non-Western” country case study on this topic. This will encourage other empirical studies from countries with various social/cultural/political backgrounds to enrich the perspective of fisheries science-policy-public interface studies globally.

Conservation of small hairtail Trichiurus japonicas by using hooks with large artificial bait: effect on the trolling line fishery - Taro Hirose; Masaki Sakurai; Shingo Watari; Michio Ogawa; Mitsutaku Makino (Fisheries Science, 2017)

A transdisciplinary research of coastal fisheries co-management: the case of the hairtail Trichiurus japonicus trolling line fishery around the Bungo Channel, Japan - Mitsutaku Makino; Shingo Watari; Taro Hirose; Kentaro Oda; Masahito Hirota; Atsushi Takei; Michio Ogawa; Hiroshi Horikawa (Fisheries Science, 2017)

Stock structure and resource management of hairtail Trichiurus japonicus based on seasonal broods around the Bungo Channel, Japan - Shingo Watari; Syunji Tokumitsu; Taro Hirose; Michio Ogawa; Mitsutaku Makino (Fisheries Science, 2017)

Re-examination of age and growth of daggertooth pike conger Muraenesox cinereus in the western Seto Inland Sea, Japan - Shingo Watari; Minoru Murata; Yuichi Hinoshita; Kazuki Mishiro; Shigeyuki Oda; Makoto Ishitani (Fisheries Science, 2013)

Age and growth of yellowstriped butterfish, Labracoglossa argentiventris, around Izu Oshima Island - Shingo WATARI; Junji YONEZAWA; Sakutaro YAMADA; Eiji TANAKA; Toshihide KITAKADO (Fisheries Science, 2005)